2001
DOI: 10.1021/om0102605
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Full-Sandwich Lanthanacarborane Complex Bearing an η7-Carboranyl Ligand, {{[η7-Me2Si(C13H9)(C2B10H11)]2YbIII}2YbII}{Na8(THF)20}

Abstract: The first full-sandwich lanthanacarborane containing an η 7 -carboranyl ligand was prepared and structurally characterized, which indicates that the arachno-carboranyl ligand can effectively stabilize the high oxidation state of the metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Reaction of equimolar amounts of 116, YbCl 3 , Na metal, and Me 3 NHCl in THF results in formation of {{[η 7 -Me 2 Si(C 13 H 9 )(C 2 B 10 H 11 )] 2 Yb III } 2 Yb II }{Na 8 -(THF) 20 } (117). 196 Addition of Me 3 NHCl is essential for isolation of 117. It is assumed that the ammonium salt protonates the appended fluorenyl anion leaving the core structure intact.…”
Section: R 2 C 2 B 10 Derivativesmentioning
confidence: 99%
“…Reaction of equimolar amounts of 116, YbCl 3 , Na metal, and Me 3 NHCl in THF results in formation of {{[η 7 -Me 2 Si(C 13 H 9 )(C 2 B 10 H 11 )] 2 Yb III } 2 Yb II }{Na 8 -(THF) 20 } (117). 196 Addition of Me 3 NHCl is essential for isolation of 117. It is assumed that the ammonium salt protonates the appended fluorenyl anion leaving the core structure intact.…”
Section: R 2 C 2 B 10 Derivativesmentioning
confidence: 99%
“…The first full sandwich lanthanacarborane containing a η 7 -carboranyl ligand, {{[η 7 -Me 2 Si(C 13 H 9 )(C 2 B 10 H 11 )] 2 Yb} 2 Yb}{Na 8 (THF) 20 } has been prepared, which is a rare example of a lanthanide complex supported only by B-H bonds. 56 Synthesis of bulky tetramethylcyclopentadienyl substituted orthocarborane ligands, exemplified by Me 2 Si(C 5 Me 4 H)(C 2 B 10 H 11 ), and their coordination chemistry with various lanthanide metals has been reported. The structures of these complexes are contrasted with the previously reported ones of Cp-functionalised ligands, and it is found that use of the bulky Cp* derived ligands result in complexes that are more unsaturated than with Cp.…”
Section: Carboranesmentioning
confidence: 99%
“…Although they are considered to be weakly coordinating anions, carbaborane compounds may be involved in agostic interactions with diverse metal centres. [30][31][32][33][34][35][36][37][38][39][40] In a recent study we reported a series of coordination complexes (either discrete, 1D or 3D polymers) of Ag(I) and smaller alkane dinitriles…”
Section: Introductionmentioning
confidence: 99%